Choice of DBMS in the conditions of fuzzy information - Нефедов, Леонид Иванович; Кононыхин, Александр Сергеевич; Петренко, Юрий Антонович; Биньковская, Анжела Борисовна (Eastern-European Journal of Enterprise Technologies, 2012)
With the help of fuzzy mathematics a selection model of DBMS are developed, thus improving the efficiency of decision making under conditions when the selection criteria set by fuzzy linguistic variables